2022
DOI: 10.1177/03009858221122500
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis is the cause of spontaneous humeral fracture in dairy cows from New Zealand

Abstract: Outbreaks of humeral fractures in dairy cows have been reported in New Zealand for several years. Gross, histologic, and histomorphometric findings in the humerus from primiparous cows with spontaneous humeral fracture were compared to age-matched control cows. Affected cows had a complete nonarticular spiral fracture of the humerus. Histologically affected humeri had a thicker growth plate with abnormal architecture, thinner cortex with increased abnormal resorption, increased resorption in the distal humerus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
(111 reference statements)
3
8
0
Order By: Relevance
“…A lower mineral/matrix ratio is reported in iliac crest bone biopsies from women and men with high-turnover osteoporosis (defined as an increased number of resorption surfaces and higher than the normal number of osteoclasts) compared to bone biopsies samples from women and men with low-turnover osteoporosis and normal bone activity ( 16 ). These results corroborate the findings from a previous analysis done on this same set of bone samples, which found that bones from cows with humeral fractures had increased abnormal resorption of cortical bone and increased bone resorption in this distal humerus ( 4 ). Furthermore, peripheral quantitative computed tomography data has found a reduction in cortical bone mineral density in the mid-diaphysis of the humerus of fractured cows ( 3 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A lower mineral/matrix ratio is reported in iliac crest bone biopsies from women and men with high-turnover osteoporosis (defined as an increased number of resorption surfaces and higher than the normal number of osteoclasts) compared to bone biopsies samples from women and men with low-turnover osteoporosis and normal bone activity ( 16 ). These results corroborate the findings from a previous analysis done on this same set of bone samples, which found that bones from cows with humeral fractures had increased abnormal resorption of cortical bone and increased bone resorption in this distal humerus ( 4 ). Furthermore, peripheral quantitative computed tomography data has found a reduction in cortical bone mineral density in the mid-diaphysis of the humerus of fractured cows ( 3 ).…”
Section: Discussionsupporting
confidence: 91%
“…For example, histological analysis of bone samples from primiparous cows with humeral fracture determined that cows with humeral fractures developed osteoporosis characterized by decreased bone volume, abnormal trabecular architecture, presence of growth arrest lines, thinner cortex with increased resorption in the cortex and distal humerus ( 1 ). These findings were associated with periods of poor bone formation (probably due to protein-calorie undernutrition), increased bone resorption associated with lactation, and periods of copper deficiency ( 1 , 4 ). Peripheral quantitative computed tomography of the mid-diaphysis of the humerus showed that fractured animals had reduced cortical bone mineral density which reduced the stress-strain index ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, we were able to measure the total collagen content and collagen crosslink content in bone from dairy cows in New Zealand which allowed us to establish important conclusions regarding the likely pathogenesis of spontaneous humeral fracture. In the case of collagen and its crosslinks, the total collagen content was significantly higher in bone from control cows and cows with adequate liver Cu concentration consistent with the histologic findings of osteoporosis reported [ 4 ]. Cows with humeral fracture and low liver Cu concentration have an increased concentration of total collagen crosslinks, DHLNL, and HYP in bone.…”
Section: Discussionsupporting
confidence: 87%
“…Another study, using peripheral quantitative computed tomography, has shown a consistent trend for reduced bone length and reduced cortical bone mineral density in primiparous cows with humeral fractures compared with age-matched controls [ 3 ]. The findings from both these studies support the hypothesis that periods of inadequate nutrition (most likely protein-calorie undernutrition) act as a contributory factor in the occurrence of humeral fractures in cows and furthermore suggest these changes are recent [ 3 , 4 ].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation